2010
DOI: 10.1097/id.0b013e3181cc48b1
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Microbiological Bacterial Seal Analysis of the Implant/Abutment Connection in Morse Taper Implants: A Comparative Study Between 2 Abutments

Abstract: We concluded that there was no statistically significant difference between the 2 models of abutment in an in vitro bacterial seal analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 9 publications
3
21
0
1
Order By: Relevance
“…These results showed that for the studied system, the maximum volume is around 0.5 µL. Other studies evaluating Morse tapered systems used 0.1 µL to 0.5 µL of volume inoculation 2,[4][5]7 . However, only two studies reported the evaluation of the best inner volume for the studied system and used the same volume for different conical systems [4][5] .…”
Section: Discussionmentioning
confidence: 57%
See 4 more Smart Citations
“…These results showed that for the studied system, the maximum volume is around 0.5 µL. Other studies evaluating Morse tapered systems used 0.1 µL to 0.5 µL of volume inoculation 2,[4][5]7 . However, only two studies reported the evaluation of the best inner volume for the studied system and used the same volume for different conical systems [4][5] .…”
Section: Discussionmentioning
confidence: 57%
“…Escherichia coli strain ATCC 35218 was selected for bacterial microleakage evaluation because it is a facultative anaerobic bacterium, able to survive in adverse situations and has a good motility, and has been used in other in vitro tests 2,5,7,[13][14] . This bacterium was cultivated in brain heart infusion broth -BHI (Biolife, Milano, Italy) for 24 h in an incubator at 37 °C (Biomatic, Porto Alegre, RS, Brazil).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations